Long‐term disease control and survival observed after stereotactic ablative body radiotherapy for oligometastatic breast cancer. (22nd June 2021) - Wijetunga, N. Ari; dos Anjos, Carlos H.; Zhi, W. Iris; Robson, Mark; Tsai, C. Jillian; Yamada, Yoshiya; Dover, Laura; Gillespie, Erin F.; Xu, Amy J.; Yang, Jonathan T.
Abstract: Purpose: We examined the characteristics of breast cancer patients with oligometastases (OM) treated with stereotactic ablative body radiotherapy (SABR) to identify factors associated with local progression, distant metastasis progression, time to subsequent therapy, progression‐free survival (PFS), and overall survival (OS). Methods: We retrospectively reviewed a single‐institution database of patients treated with radiotherapy between 2008 and 2018 and identified 79 patients who received SABR to OM. Twenty‐seven patients had genetic testing of metastatic tumors using an institutional targeted sequencing platform. Kaplan–Meier analysis, Cox regression, and competing risk models were used to compare clinical and genetic correlates with outcomes. Results: Median follow‐up was 50 months (IQR: 29–66) with 67% of patients alive at the last follow‐up. Of the 65% of patients who progressed, 82% progressed outside of the radiation field, 18% experienced local failure, and 80% had oligoprogression. Median OS was 86 months (IQR: 29–66), and PFS was 33 months (IQR: 10–38). Less than 5 years from diagnosis to SABR and triple‐negative breast cancer (TNBC) were associated with worse OS. Advanced T stage, any prior chemotherapy, and TNBC were associated with worse PFS. Alterations in CEBPB, RB1, TBX3, PTEN, and CDK4 were associated with worse survival outcomes. Conclusion: Long‐term systemic disease control and survival can be achieved with SABR for oligometastatic breast cancer. Hormone receptor‐positive patients with a long disease interval from initial diagnosis and limited systemic progression history may be ideal for SABR to all sites of disease. Abstract : Through a retrospective review of our institution's oligometastatic breast cancer patients who were treated with stereotactic ablative radiotherapy, we identified clinical and genetic correlates with survival outcomes, including overall survival and progression‐free survival. Our work substantiates the role of high dose targeted radiotherapy in metastatic breast cancer patients with a low burden of disease, and our findings provide insight into optimal patient selection and elucidate clinical outcomes.